Prevalence and Socio-Demographic Correlates of Body Weight Categories Among South African Women of Reproductive Age: A Cross-Sectional Study - Akokuwebe, Monica Ewomazino; Idemudia, Erhabor Sunday (Frontiers in Public Health, 2021)
Background: The shift in disease patterns has been connected with increased body weight burden, becoming a major public health concern in South Africa, as previous studies have assessed overweight or obesity among certain populations. However, little is known about body weights’ burden (underweight, overweight and obesity) among women aged 15-49 years. Therefore, this study was conducted to identify the prevalence and its associated sociodemographic correlates of body weight categories among women of reproductive age in South Africa. Methods: The present study used the South Africa Demographic Health Survey (SADHS) data for 2016. A total of 3263 of women of reproductive age were included in the analysis. Both bivariable and multivariable logistics regression were performed to determine the prevalence and sociodemographic correlates of body weight categories among women in South Africa. The OR with a 95% CI was estimated for potential determinants included in the final model. Results: The overall prevalence of body weight categories were 66.5% (underweight–4.9%; overweight–27.1%; and obesity– 34.5%, p<0.05). The identified factors associated with underweight among women of reproductive age were those from ‘Other’ population group (UOR 2.05: 95% CI 1.32-3.19; AOR 2.65: 95% CI 1.40-5.00), rural residence (UOR 1.14: 95% CI 0.81-1.61; AOR 1.23: 95% CI 0.75-2.02) and Northern Cape Province (UOR 2.18; 95% CI 0.92-5.14; AOR 1.58: 95% CI 0.65-3.87). For overweight/obesity, the main factors were those aged 45–49 years (UOR 12.83: 95% CI 9.19-17.93; AOR 10.73: 95% CI 7.41-15.52), tertiary education (UOR 1.54: 95% CI 1.12-2.11; AOR 1.41: 95% CI 0.97-2.03), and residing in Eastern Cape (AOR 1.27: 95% CI 0.82-1.99) and KwaZulu-Natal Provinces (AOR 1.20: 95% CI 0.78-1.84). Conclusion: The findings presented in this study indicate concurrence of underweight and overweight/obesity among women aged 15-49 years in South Africa, despite underweight prevalence is on the decline, yet overweight/obesity is increasing over time. The health implications of body weight burden needs abrupt and effective interventions, focusing on rural, education, population group, old age 45-49 years, and Provinces (Northern Cape, Eastern Cape and KwaZulu-Natal) ─the high-risk groups identified herein are of most importance, to curb the growing burden among South African women.